Proceedings of the 2021 Conference on Human Information Interaction and Retrieval 2021
DOI: 10.1145/3406522.3446026
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Cost, Effort, and Load in Information Seeking and Retrieval

Abstract: When performing Information Seeking and Retrieval (ISR) activities, people submit queries, examine results, assess documents and engage with the information to make decisions and complete tasks. All these activities come at a "cost", but within the field of ISR there is no universally accepted definition of the concepts of Cost, Effort and Load (CEL). Instead, researchers have used the same terms interchangeably to describe similar but also different concepts. This lack of shared understanding has led to a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
(163 reference statements)
0
10
0
Order By: Relevance
“…To calculate the cost related to this assumed gain, we use a time‐oriented metric (McGregor et al, 2021). Because of the time pressure legal professionals work under this appears to be the most suitable representation of cost or effort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the cost related to this assumed gain, we use a time‐oriented metric (McGregor et al, 2021). Because of the time pressure legal professionals work under this appears to be the most suitable representation of cost or effort.…”
Section: Methodsmentioning
confidence: 99%
“…This sum of costs is then offset to the gains of the relevant documents found. McGregor et al (2021) differentiate between load, effort, and cost. Load is taken to refer to the total amount of resources used to complete the task, internally and externally.…”
Section: Usage In Evaluationmentioning
confidence: 99%
“…Those results seem moderated by expertise within VR and the task demands (Aksoy et al 2019;Luong et al 2019;Armougum et al 2019). For instance, outside of VR, when time and load on the resources are high, humans hit the maximum resource allocation capacity (McGregor et al 2021).…”
Section: Mental Overload and Working In Vrmentioning
confidence: 99%
“…The demands imposed during the search process are well recognised, and numerous studies have demonstrated that the cost, effort, and load (CEL) experienced during the search process is affected by not only the search task [27,91,120], but also the system [21,23,37] and the individual characteristics [24,57] of the user. Despite this recognition, our recent perspectives paper [97] highlighted two prominent challenges facing the ISR community in regard to CEL research. The first challenge relates to the general lack of consensus regarding cost, effort, and load definition, which has ultimately left the field with no universal definitions to describe these constructs.…”
Section: Introductionmentioning
confidence: 99%